Inovasi Siap CSO pada Kantor Pelayanan Perbendaharaan Negara (KPPN) Kabupaten Pamekasan - Erika Octaviani Putri Alamsyah Erika; Nur Fathin Luaylik Fathin (Universitas Madura, 2026)
Purpose: This study aims to analyze the innovation of SIAP CSO (Attendance Information System and Customer Service Officer Consultation Service) at KPPN Pamekasan in improving the effectiveness of attendance management and the quality of consultation services for service users (work partners). Research Methofology: This research uses a qualitative descriptive approach carried out over three months at the State Treasury Service Office (KPPN) Pamekasan. Results: This study found the SIAP CSO website-based innovation that facilitates the process of attendance recording, consultation data management, and service monitoring more quickly, accurately, and in an integrated manner. In addition, SIAP CSO improves services through easier access to more organized information and data. Conclusions: SIAP CSO provides positive impacts in the form of increased service efficiency, data transparency, and recording accuracy, while also strengthening the role of Customer Service Officers in providing faster and more targeted consultation to work units. This innovation becomes a strategic step in realizing digital-based and effective services at KPPN Pamekasan. Limitations: This research is limited to the SIAP CSO innovation that uses Microsoft Forms and Microsoft 365 Excel Collaboration Tools. The resulting data being very basic, and the scope of implementation being limited to a single innovation, so it is not yet fully integrated with other service systems. Contribution: This research contributes to KPPN Pamekasan and service users (partners) in improving understanding of the use of digital-based information systems to support more effective, accurate, and transparent attendance management and consultation services.